Pengaruh Inflasi ,Pertumbuhan Ekonomi dan Kebutuhan Hidup Layak terhadap Upah Minimum Provinsi (UMP) Di Provinsi Kalimantan Selatan - S Sayyidah; Muhammad Effendi (PPJP Universitas Lambung Mangkurat, 2020)
This study aims to (1) determine the influence of the inflation, economic growth, and decent living needs simultaneously to Provincial Minimum Wages in the south Borneo Province; (2) find out the dominant factor in influencing Provincial Minimum Wages in South Borneo Province; Purpose including in type purpose descriptive quantitative. While the location purpose is the province south Borneo, and the goal is inflation, economic growth, decent living needs, and provincial minimum wages in the South Borneo Province in 2004-2018. Data obtained will be analyzed by multiple linear regression using the Program Eviews version 10.This study shows that the (1) Inflation, Economic Growth, and Decent Living Needs at the same time has a significant impact on Provincial Minimum Wages in the South Borneo Province in 2004-2018. (2) This study also indicates that Decent Living Needs is the dominant factor affecting Provincial Minimum in South Borneo Province in 2004-2018.